A polymorphism in the 3′-untranslated region of the matrix metallopeptidase 9 gene is associated with susceptibility to idiopathic calcium nephrolithiasis in the Chinese population. Issue 12 (December 2020) - Bu, Qiang; Zhu, Yu; Chen, Qiao-yun; Li, Hao; Pan, Yan
Objective: To investigate whether single nucleotide polymorphisms (SNPs) in the 3′ untranslated region (UTR) of the matrix metallopeptidase 9 gene ( MMP9 ) are associated with susceptibility to calcium oxalate stones. Methods: A total of 428 patients with kidney stone disease (KSD) and 450 control individuals were enrolled. Three MMP9 SNPs (rs20544, rs9509, and rs1056628) were genotyped, and MMP9 mRNA and protein expression was determined in patients and controls. The dual luciferase reporter gene assay was conducted by transfecting HEK293 cells with miR-491-5p mimics and plasmids containing MMP9 with rs1056628 AA/CC genotypes. Results: The rs1056628 CC genotype was significantly increased in KSD patients compared with controls (CC vs AA: odds ratio [OR] = 2.279, 95% confidence interval [CI] = 1.048–4.956). The rs1056628 C allele frequency was higher in KSD patients than controls. The increased KSD risks associated with rs1056628 were more evident in individuals aged <30 years (OR = 3.504, 95% CI = 1.102–11.139) and men (OR = 2.522, 95% CI = 1.004–6.334). mRNA and protein levels of MMP9 were significantly higher in KSD patients with the CC genotype than in those with the AA genotype. Conclusion: This study demonstrates that MMP9 SNP rs1056628 is associated with a significant KSD risk in Chinese Han individuals.